Access to 2‐Arylquinazolin‐4(3H)‐ones through Intramolecular Oxidative C(sp3)−H/N−H Cross‐Coupling Mediated by I2/DMSO. Issue 4 (26th November 2021) - Wen, Simiaomiao; Du, Yifan; Liu, Yiwen; Cui, Xiaofeng; Liu, Qixing; Zhou, Haifeng
Abstract: A novel approach for the synthesis of 2‐arylquinazolin‐4(3H)‐ones was developed. A series of title compounds were obtained with good functional group tolerance and good yields by I2 /DMSO‐mediated intramolecular oxidative cross‐coupling of 2‐(benzylamino)benzamides to form C=N double bonds. This method was applicable for gram‐scale synthesis. A proposed reaction pathway based on some control experiments was also provided. Abstract : A practical approach for preparing 2‐arylquinazolin‐4(3H)‐ones by an I2/DMSO‐mediated intramolecular oxidative cross‐coupling of 2‐(benzylamino)benzamides to form C=N bonds has been developed.